Dark fire - Sansom, C. J. (Sansom, C. J. Shardlake series., 2005)
When a friend's niece is charged with murder and threatened with torture for her refusal to speak, 1540 lawyer Matthew Shardlake is granted a reprieve to investigate the case if he will also accept a dangerous assignment to find a legendary weapon.